2007
DOI: 10.1016/j.intimp.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Active monomers of human β-tryptase have expanded substrate specificities

Abstract: Abstractβ-Tryptase, a product of the TPSAB1 and TPSB2 genes, is a trypsin-like serine protease that is a major and selective component of the secretory granules of all human mast cells, accounting for as much as 25% of cell protein. Once mast cells are activated, β-tryptase is released along with histamine and heparin proteoglycan. β-Tryptase is a unique enzyme with a homotetrameric structure in which active sites face into the central cavity of the four monomers, stabilized by heparin-proteoglycan. This struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 78 publications
2
12
0
1
Order By: Relevance
“…To see whether inhibition was simply due to a shift in pH optimum or a change in substrate specificity, we determined bI-tryptase activity at physiological heparin levels ($1 mg/mL) and found that anti-tryptase was also a potent and complete inhibitor at pH 7.0 and 8.0 ( Figure S3B). However, there was a small amount of residual activity at pH 6.0 from monomers that was inhibited by aprotinin ( Figure S3B), in accord with previous data (Fajardo and Pejler, 2003;Fukuoka and Schwartz, 2004;Fukuoka and Schwartz, 2007). However, monomers are $50-fold less active than tetramers at neutral pH and strongly dependent upon heparin (Maun et al, 2018) and rapidly inactivated by protease inhibitors (Fukuoka and Schwartz, 2004), thus thought not to be physiologically relevant.…”
Section: Generation Of a Humanized Anti-tryptase Antibody With Potentsupporting
confidence: 89%
“…To see whether inhibition was simply due to a shift in pH optimum or a change in substrate specificity, we determined bI-tryptase activity at physiological heparin levels ($1 mg/mL) and found that anti-tryptase was also a potent and complete inhibitor at pH 7.0 and 8.0 ( Figure S3B). However, there was a small amount of residual activity at pH 6.0 from monomers that was inhibited by aprotinin ( Figure S3B), in accord with previous data (Fajardo and Pejler, 2003;Fukuoka and Schwartz, 2004;Fukuoka and Schwartz, 2007). However, monomers are $50-fold less active than tetramers at neutral pH and strongly dependent upon heparin (Maun et al, 2018) and rapidly inactivated by protease inhibitors (Fukuoka and Schwartz, 2004), thus thought not to be physiologically relevant.…”
Section: Generation Of a Humanized Anti-tryptase Antibody With Potentsupporting
confidence: 89%
“…In addition, we did not systematically evaluate other potential reasons for increased ST levels, such as diverse haematological disorders (e.g. acute myeloid leukaemia) (23,35), haemodialysis (36), or other allergic conditions, such as chronic urticaria (37) or anaphylactic reactions, which cause transient elevation of ß-tryptase (38). The extent of infiuence of these conditions in our population remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are locally activated and released into the microenvironment, where they can act on the various extracellular targets, i.e. activate pro-MMPs, cleave extracellular peptides and degrade lipoproteins and fibronectin [92]. Circulating tryptase levels are positively correlated with subclinical atherosclerosis and have a positive correlation with obesity and insulin resistance [93].…”
Section: Receptor Cleavage In Diabetes and Insulin Resistancementioning
confidence: 99%